Friedrich István és az 1922-es választójogi rendelet - Köpfler, Balázs (Közép-Európai Közlemények, 2019)
Opposition parties fought for a great voteing reform for several decades. They could not be successful. Most part of the political elit feered anykind of changes. Before the First World War, István Tisza, the prime minister of Hungary blocked every initiative to change the voteing rules, because he thought already a little change could be catastrophic. István Friedrich participetied in the sufffrage movement by Independant Party. After the first World War Hungary tried to reorganize itself. On the autum of 1919 hungarian goverment (its prime minister was István Friedrich) introduced new voting regulations that made possible more people to vote. After the first election two party exceed. One was the smallholders party. The other was Christian National Union Party. In the first term of the National Assembly the political system was not stabilized. After the first attempt of Charles the Fourth to returne Istvan Bethlen became prime minister. He wanted to stabilized the whole political system to start a reform process. For the that he started to build up a ruling party and reform the voting system. Friedrich and the opposition parties tried to stop Bethlen’s plan. They failed. Bethlen installed a new voting system with open ballott. That system helped the ruling party to hold the power. It did not change for almost twenty years. Istvan Friedrich as a member of the parlament always stand out for secret ballott system. He belived with that Hungary could become more democratic and prosperus.